Attempted Criminal Offence - Jovašević, Dragan (Zbornik Instituta za kriminološka i sociološka istraživanja, 2015)
Between the moment when the decision has been made to commit a criminal offence and the moment when the consequence in the outer world has been caused, there are several phases: decision, preparatory activities, attempt and completed criminal offence. An attempt represents a specific phase in the commission of a criminal offence and includes the activity that constitutes the offence (made upon a previously prepared decision), but without causing the actual consequence. It is a potential, facultative phase that is punishable only in cases of more serious criminal offences, for which punishment is prescribed by the law. In this paper, the term, types, characteristics, contents and legal nature of attempted criminal offence are discussed.